Dark Channel Prior (DCP) based Bangla car plate detection and recognition in foggy weather - Nasim, Hamim Ibne; Printia, Fateha Jannat; Himel, Mahamudul Hasan; Rashid, Rubaba; Chowdhury, Iffat Jahan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.